Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan tentang Gizi Seimbang pada Orang Tua yang Memiliki Anak Usia 4-6 Tahun di TK Parentas 2 Kota Palangka Raya: The Influence of Health Education on the Level of Knowledge about Balanced Nutrition in Parents who Have Children Aged 4-6 Years at Parentas Kindergarten 2 Palangka Raya - Indriani Indriani; Desi Kumala; Junjung Junjung (Jurnal Surya Medika (JSM), 2022)
Background: A parent's knowledge of balanced nutrition is essential for achieving well-balanced nutrition in children aged 4-6. The level of knowledge and role of the mother or parents are important in fulfilling the balanced nutrition in preschool children so that growth, development, intelligence, nutritional status, and health are fulfilled well. Objectives: This study aimed to determine the influence of health education on the level of knowledge about balanced nutrition in parents who have children aged 4 to 6 years old (in Parentas kindergarten 2 Palangka Raya). Methods: The research design used in this research is Pre-Experimental with a pre-post test approach, with the sampling technique used being total sampling. The population in this study is parents with children aged 4 to 6 years old in Parentas kindergarten 2 Palangka Raya as many as 44 respondents. The data was collected by using questionnaires. Results: The result of this research is obtained p-value is 0.000 <α 0.05, which means there is a significant influence of health education on the level of knowledge about balanced nutrition in parents who have children aged 4 to 6 years old (in Parentas kindergarten 2 Palangka Raya). Conclusion: Based on the results of this research, parents with good knowledge about balanced nutrition can affect the achievement of balanced nutrition in children aged 4-6 years.